2019
DOI: 10.1111/sum.12545
|View full text |Cite
|
Sign up to set email alerts
|

Co‐selection for antibiotic resistance genes is induced in a soil amended with zinc

Abstract: The likelihood of co‐selection for antibiotic resistance induced by heavy metals is a potential threat to human health, however, direct evidence of heavy metal‐induced co‐selection of antibiotic resistance is lacking in soil. By using a metagenomic sequencing approach, zinc (Zn) driven co‐selection of antibiotic resistance genes (ARGs) in soil was investigated through a microcosm experiment where Zn salts were added at different levels. The results showed that the abundance and diversity of ARGs had a tendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The results of this study are consistent with the conclusions of Zhang et al and Chen et al [ 55 , 56 ]. Soil acidity also affected the abundance of ARGs, which was mainly because lower pH increased the solubility of pollutants, and a higher concentration of pollutants affected the metabolism of bacteria, which has been confirmed by a previous study [ 51 ]. In addition, soil pH and organic matter also contributed significantly to the relative abundance of intl1 and intl2 genes, and the contribution of pH and organic matter to the relative abundance of the intl1 gene was more significant than that of intl2 gene.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The results of this study are consistent with the conclusions of Zhang et al and Chen et al [ 55 , 56 ]. Soil acidity also affected the abundance of ARGs, which was mainly because lower pH increased the solubility of pollutants, and a higher concentration of pollutants affected the metabolism of bacteria, which has been confirmed by a previous study [ 51 ]. In addition, soil pH and organic matter also contributed significantly to the relative abundance of intl1 and intl2 genes, and the contribution of pH and organic matter to the relative abundance of the intl1 gene was more significant than that of intl2 gene.…”
Section: Resultssupporting
confidence: 77%
“…The total relative abundance of ARGs was positively correlated with Pb concentration under OTC-added to the soil. This might be because Pb exposure significantly increased the abundance of MGEs (integrons and inserts) and the overall relative abundance of ARGs [ 51 ]. In contrast, this study found that lower concentrations of Pb did not contribute to enhancing the expression of MGEs, resulting in a lower overall relative abundance of ARGs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cadmium was shown to increase the abundance of ARGs and intI1 in oxytetracycline polluted soil and lettuce tissue (Guo et al, 2021). Tongyi et al (2020) observed that the abundance of intI1, insertion sequences, and ARGs increased, along with the gradient of zinc concentration in the soil, indicating that zinc can affect ARG mobility. In urban soils heavy metals, such as arsenic, cadmium, cobalt, chromium, copper, mercury, nickel and zinc, can alter MGE abundances (Zhao et al, 2019b).…”
Section: Heavy Metals Influence the Abundance And Spread Of Mobile Ge...mentioning
confidence: 94%
“…Microbial communities may be shaped by exposure to different agents and furthermore metals within natural environments have been shown to significantly impact on the structure of microbial communities [181]. There is also some evidence that the presence of metals may have a positive effect on the HGT potential of ARGs in soil [174,[182][183][184][185]. How metals enhance the mechanism of genetic transfer is not clear, although there is some evidence that livestock-associated bacteria may carry more MGEs than bacteria from other sources (such as clinical environments) [183].…”
Section: Impact Of Metals Used During Food Animal Production On Amr I...mentioning
confidence: 99%